A research project with students of Information and Communication Technology in obligatory secondary education: virtual reconstruction of the thermal area of the roman villa of Balazote (Albacete) - Pilar Mediano Serrano (Centro de Estudios Financieros, 2016)
The optional subject Information and Communication Technology (ICT) in obligatory secondary education is fundamentally about how to use applications. The software related to this subject is based on: photo editing programs, 3D constructions, sound editing and video editing. These can be viewed in isolation and independently or as a part of a comprehensive project in which students have to handle all of them at once. This article will explain a project with students: the virtual reconstruction of the thermal area of the roman villa of Balazote (Albacete). The goal was to improve student motivation and get actively involved in their learning process. Students used computers and classes of the course to conduct such research. First, the necessary information was sought, and then, based on that information and using different software about virtual reconstruction and recording and editing films: Gimp, SketchUP, Movie Maker, etc., our film was made. The result of this work is a film consisting of a virtual tour inside the roman villa.